Development of RME-Based Electronic Student Worksheet on Peatland Context for Pythagoras Theorem in Grade VIII Junior High School - Setri Oktavia; Loy Cindy Br Milala; Putri Sasalia S.; Sugiharto Sugiharto (Pendidikan Matematika STKIP Kusuma Negara, 2026)
The learning approach used in the following research is the Realistic Mathematics Education (RME) approach by utilizing peatlands as a context and digital media as a tool. The learning media developed is the electronic student worksheet with the help of liveworksheets in its use. Currently, schools have not developed electronic student worksheet assisted by liveworksheets and have not used peatlands as a context. The purpose of the following this study is conducted to produce a product as electronic student worksheet proven to be valid and practical for implementation, so that students are motivated in learning. The following research uses 4 of the 5 ADDIE stages. The results of the study show that the developed electronic student worksheet is feasible and practical to use with an average of 91% and 82% from 2 validators respectively with very feasible criteria. According to the results of the calculation of the response questionnaire from 30 students and 1 educator, it states that electronic student worksheet is practically used in learning with an average of 89% and 88% respectively. It is hoped that future researchers can use the following electronic student worksheet to see its practicality from year to year.